Love and Kindness during wartime in Markus Zusak’s The Book Thief (مجلة ديالى للبحوث الانسانية, 2025)
The current study sheds light on the importance of love and kindness during the hard times of wars. The study calls for greater attention to consider the human side and human emotions like love, compassion and kindness for being the best shelters and ways of survival against the destruction of wars. The paper presents an analytical study to the historical novel under study, Markus Zusak’s The Book Thief  (2005) by exploring the characters and clarifying how their life experiences shaped their destines using the Sociopolitical Development Theory. The novel demonstrates the impact of the political conflicts and wars on societies and depict the characters’ suffering, struggle and resilience in the face of oppression and persecution. The study aims to prove that even through darkness and despair of bleak situations, there can be a glimmer of hope out of unbreakable bonds of love and friendship.